A Model of Monetary Policy and Risk Premia - DRECHSLER, ITAMAR; SAVOV, ALEXI; SCHNABL, PHILIPP (Journal of Finance, 2018)
ABSTRACT We develop a dynamic asset pricing model in which monetary policy affects the risk premium component of the cost of capital. Risk‐tolerant agents (banks) borrow from risk‐averse agents (i.e., take deposits) to fund levered investments. Leverage exposes banks to funding risk, which they insure by holding liquidity buffers. By changing the nominal rate the central bank influences the liquidity premium, and hence the cost of taking leverage. Lower nominal rates make liquidity cheaper and raise leverage, resulting in lower risk premia and higher asset prices, volatility, investment, and growth. We analyze forward guidance, a “Greenspan put,” and the yield curve.